Sustainable organizational change : the social change model for systems - Burton, Joshua D.; Carter, Barbara (Routledge, 2026)
The Social Change Model for Systems (SCMS) is a robust system for facilitating organizational change. SCMS integrates technical and social controls to ensure organizational effectiveness. This book introduces SCMS as an alternative to traditional control systems, emphasizing the interplay between diagnostic and interactive social controls to shape organizational belief and boundary systems. SCMS promotes a structured, evidence-based method for assessing organizational climate, addressing challenges, incorporating social characteristics, and developing effective social strategies. The model highlights the importance of ongoing reassessment and iterative change management through frameworks such as Agile, ADKAR, and the Plan-Do-Study-Act cycle. Key benefits of SCMS include fostering trust, equity, and engagement; improving decision-making; and enhancing employee satisfaction. The study provides practical applications of SCMS through case studies, demonstrating SCMS's role in improving work unit climates and organizational performance. By bridging the gap between hierarchical control and methods that include employee input, SCMS provides a flexible, adaptive strategy for leaders and HR managers to implement sustainable organizational changes.
Keywords: Corporate culture -- Social aspects.; Organizational change -- Social aspects.; Sustainable development -- Social aspects.; elektronické knihy; electronic books